The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1365-2605.2001.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin affinity of the seminiferous epithelium in healthy and cryptorchid post‐pubertal boars

Abstract: The present study describes the sugar content of the seminiferous epithelium, using lectin histochemistry, in healthy boars and in boars with unilateral and bilateral abdominal cryptorchidism. In healthy boars the apical cytoplasm of Sertoli cells exhibited abundant glucosyl (Con A and WGA lectins), galactosyl (HPA, DBA, SBA and PNA lectins), and fucosyl (AAA lectin) residues. Spermatogonia and spermatocytes contained abundant glucosyl (Con A and WGA lectins) and fucosyl (AAA lectin) residues. In spermatids, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(128 reference statements)
2
14
2
Order By: Relevance
“…As the primitive cells differentiated, DBA staining was lost, which explains why the spermatogonia showed no affinity at all. Similarly, DBA does not bind to spermatogonia in postpubertal boar testes [34]. UCHL1 expression was restricted to germ cells, as reported previously [32].…”
Section: Histochemistrysupporting
confidence: 80%
See 1 more Smart Citation
“…As the primitive cells differentiated, DBA staining was lost, which explains why the spermatogonia showed no affinity at all. Similarly, DBA does not bind to spermatogonia in postpubertal boar testes [34]. UCHL1 expression was restricted to germ cells, as reported previously [32].…”
Section: Histochemistrysupporting
confidence: 80%
“…The anti-SSEA-1 and EMA-1 monoclonal antibodies and DBA bind specifically to the large round PGCs of the genital ridge in pigs [33]. In the postpubertal boar testis, DBA binds weakly to the apical cytoplasm of Sertoli cells [34]. In neonatal human testis, DBA binds to spermatogonia and Leydig cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…SJA has specificity toward carbohydrate structures terminating with N-acetylgalactosamine and galactose residues. Finally, VVA recognizes preferentially a-or b-linked terminal Nacetylgalactosamine (Pinart et al, 2001;Nagano et al, 2005). All lectins of the third group generally stained testis cells weakly (note that the different intensities in Fig.…”
Section: Histological Analysismentioning
confidence: 86%
“…In our study, we found very few DBA-positive cells in porcine testis, which is in agreement with Goel et al (2007), who also found a small number of DBA-positive cells in testis of a 5-month-old pig. Pinart et al (2001) reported no DBA affinity to cells of the seminiferous epithelium in 9-month-old postpubertal porcine testes, indicating that in older boars the epitope bound by DBA is no longer present in spermatogonia. Very few cells bound DBA in the horse testis (Ha et al 2003).…”
Section: Discussionmentioning
confidence: 98%